Download presentation

1
**Sum and Product of Roots**

Quadratic Functions Sum and Product of Roots

2
Purpose Find sum/product of roots without knowing the actual value of x. Use the sum/product of roots to solve for other results

3
Derivation of Formula Given α and β are roots of a quadratic equation, we can infer that x1 = α and x2 = β , where α and β are just some numbers. For example, x2 – 5x + 6 = 0 has roots α and β means that α = 2 and β = 3

4
However… Sometimes, we do not need the values of x to help us solve the problem. Knowing the relationship between the quadratic equation and its roots helps us save time

5
**Derivation of Formula This tells us that: (x – α)(x – β) = 0**

ax2 + bx + c = 0 has roots α and β –(1) This tells us that: (x – α)(x – β) = 0 Expanding, we have: x2 – αx – βx + αβ = 0 x2 – (α + β)x + αβ = 0 So, if we compare the above with (1): x x + = 0 Result: αβ = , α + β =

6
**In other words… x2 – (α + β)x + αβ = 0**

ax2 + bx + c = 0 has roots α and β x2 – (α + β)x + αβ = 0 x2 – (sum of roots)x + product of roots = 0

7
**Application – Example 1 (TB Pg 55)**

2x2 + 6x – 3 = 0 has roots α and β, find the value of (a) Without finding α and β, we know the value for α + β and αβ α + β = – 3 and αβ = – 3/2 Hence,

8
**Application – Example 1 (TB Pg 55)**

2x2 + 6x – 3 = 0 has roots α and β, find the value of (b) We already know that: α + β = – 3 and αβ = – 3/2 Expanding (b), we have

9
**Application – Example 2 (TB Pg 55)**

x2 – 2x – 4 = 0 has roots α and β, find the value of (a) Step 1: α + β = 2 and αβ = – 4 To find (a), we use the algebraic property Rearranging:

10
**Application – Example 2 (TB Pg 55)**

x2 – 2x – 4 = 0 has roots α and β, find the value of (b) Step 1: α + β = 2 and αβ = – 4 To find (b), we use the algebraic property Rearranging: Hence, α − β =

11
**Application – Example 2 (TB Pg 55)**

x2 – 2x – 4 = 0 has roots α and β, find the value of (c) Step 1: α + β = 2 and αβ = – 4 To find (a), we use the algebraic property Rearranging:

12
**Application – Example 3 (TB Pg 56)**

2x2 + 4x – 1 = 0 has roots α and β, form the equation with roots α2 and β2 Remember! x2 – (sum of roots)x + product of roots = 0 x2 – (α2 + β2)x + α2β2 = 0 So in order to get the equation, I must find α2 + β2 and α2β2 How?

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google